2019
DOI: 10.1007/s11661-019-05343-5
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Iron-Rich Intermetallic Phases in Al-7Si-Mg: Influence of Cooling Rate and Strontium Modification

Abstract: The influence of cooling rate on the formation of iron-rich intermetallic phases during solidification of unmodified and strontium-modified Al-7Si-0.3Mg alloys has been investigated. The effect of strontium on the intermetallic phases was evaluated in unquenched and quenched samples. Samples were quenched before the start of the Al-Si eutectic reaction, along the Al-Si eutectic reaction and just after the end of solidification. The results show that the addition of strontium increased the size of both b-Al 5 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…An agglomeration of Al2O3 nanoparticles was also reported in [37,40]. The needle-like intermetallic phases present in the microstructures of both matrix alloy and composite are β-Al5FeSi which are also noticed in the literature [36,[41][42][43]. Irregularly shaped light-coloured phases contain Al-Ni-Cu-(Fe).…”
Section: Methodsmentioning
confidence: 54%
“…An agglomeration of Al2O3 nanoparticles was also reported in [37,40]. The needle-like intermetallic phases present in the microstructures of both matrix alloy and composite are β-Al5FeSi which are also noticed in the literature [36,[41][42][43]. Irregularly shaped light-coloured phases contain Al-Ni-Cu-(Fe).…”
Section: Methodsmentioning
confidence: 54%
“…The morphology of the eutectic Si was observed at a higher magnification using deep-etched samples, as shown in Figure 4. As seen in Figure 4a,b, sample A exhibited the expected eutectic Si coarse plate shape that commonly grows epitaxially from the α-Al dendrites and induces stress concentration that is detrimental to strength and ductility [20]. Even though the shape of the eutectic Si of sample B was similar to sample A, thinner plates were found in the US-treated (sample B) mostly due to the chill modification effect promoted by US treatment.…”
Section: Resultsmentioning
confidence: 94%
“…Usually, the β and π-Fe phases are produced as plate-like and Chinese-script morphologies, respectively during the solidification [47]. Nevertheless, Santos [62] and Caceres [52] revealed that Sr modification of A356/357 alloy poisons the β-Fe phase nucleation sites and promotes the formation of the π-Fe phase as plate-like morphologies. Therefore, it is quite logical that the π-Fe phase in B-0 and B-1 alloys appeared as plate/needle-like morphologies due to the Sr modification.…”
Section: Discussionmentioning
confidence: 99%